ANALISIS EFISIENSI BOILER UNIT 2 DAN 4 DI PT. PLN (PERSERO) WIL. KALSELTENG SEKTOR PLTU ASAM-ASAM - Aries Aditya Kurniawan; Aqli Mursadin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2019)
Boiler is a tool used to produce steam / steam for various purposes. The water in the boiler is heated by heat from the fuel combustion (other heat source) resulting in heat transfer from the heat source to the water causing the water to become hot or transformed into steam. Direct Methods Also known as